The Implementation of Cooperative Learning Type Numbered Heads Together to Improved Students Learning Competence of BiologyClass X MIA 2 SMA Negeri 2 Solok Selatan - Ramadhan Sumarmin; Pardismi Pardismi; Gusril Gusril (Bioeducation Journal, 2017)
Students’ competency in learning of Biology at class X MIA2 of SMAN 2 Solok Selatan are not optimum yet. It is necessary to increase students’ competency by implementing cooperative learning model of Numbered Heads Together type. This research aim to approve students’ competency in learning Biology by applied of Numbered Heads Together Model. This research done in two cycles ( P1 and P2 plus 1 precycle P0). Each cycle consisted of three lessons. There are four phases in the cycle; planning, action, observation, and reflection. The instruments of the research were observation sheet on the teachers activities, learning competence and questionnaire research. The data was collected through observation and a learning achievement test. The data analyzed qualitatively and quantitatively. The results showed that the students’ activity and competency were increase. The students’ achievement involved the cognitive, that is the number of students who passed were P0 64,00%, P1 76,00% to P2 88,00%. The students affective were P0 56,00%, P1 63,07% to P2 77,73%. and the students’ psychomotoric were P0 59,00%, P1 68,28% to P2 78,71%. Research questionnaire containing statements student responses to the application of Numbered Heads Together Model increased from P1 80.86% to P2 84.93% . It can be concluded that the using of Numbered Heads Together increased students’ competency in learning Biology at X MIA2 class of SMAN 2 Solok Selatan.